Mycobacteriophage-antibiotic therapy promotes enhanced clearance of drug-resistant Mycobacterium abscessus - Matt D. Johansen; Matthéo Alcaraz; Rebekah M. Dedrick; Françoise Roquet-Banères; Claire Hamela; Graham F. Hatfull; Laurent Kremer (The Company of Biologists, 2021)
Infection by multidrug-resistant Mycobacterium abscessus is increasingly prevalent in cystic fibrosis (CF) patients, leaving clinicians with few therapeutic options. A compassionate study showed the clinical improvement of a CF patient with a disseminated M. abscessus (GD01) infection, following injection of a phage cocktail, including phage Muddy. Broadening the use of phage therapy in patients as a potential antibacterial alternative necessitates the development of biological models to improve the reliability and successful prediction of phage therapy in the clinic. Herein, we demonstrate that Muddy very efficiently lyses GD01 in vitro, an effect substantially increased with standard drugs. Remarkably, this cooperative activity was retained in an M. abscessus model of infection in CFTR-depleted zebrafish, associated with a striking increase in larval survival and reduction in pathological signs. The activity of Muddy was lost in macrophage-ablated larvae, suggesting that successful phage therapy relies on functional innate immunity. CFTR-depleted zebrafish represent a practical model to rapidly assess phage treatment efficacy against M. abscessus isolates, allowing the identification of drug combinations accompanying phage therapy and treatment prediction in patients. This article has an associated First Person interview with the first author of the paper.